Functional characterization of BcrR: a one-component transmembrane signal transduction system for bacitracin resistance. Issue 4 (19th February 2019) - Darnell, Rachel L.; Nakatani, Yoshio; Knottenbelt, Melanie K.; Gebhard, Susanne; Cook, Gregory M.
Abstract : Bacitracin is a cell wall targeting antimicrobial with clinical and agricultural applications. With the growing mismatch between antimicrobial resistance and development, it is essential we understand the molecular mechanisms of resistance in order to prioritize and generate new effective antimicrobials. BcrR is a unique membrane-bound one-component system that regulates high-level bacitracin resistance in Enterococcus faecalis . In the presence of bacitracin, BcrR activates transcription of the bcrABD operon conferring resistance through a putative ATP-binding cassette (ABC) transporter (BcrAB). BcrR has three putative functional domains, an N-terminal helix–turn–helix DNA-binding domain, an intermediate oligomerization domain and a C-terminal transmembrane domain. However, the molecular mechanisms of signal transduction remain unknown. Random mutagenesis of bcrR was performed to generate loss- and gain-of-function mutants using transcriptional reporters fused to the target promoter P bcrA . Fifteen unique mutants were isolated across all three proposed functional domains, comprising 14 loss-of-function and one gain-of-function mutant. The gain-of-function variant (G64D) mapped to the putative dimerization domain of BcrR, and functional analyses indicated that the G64D mutant constitutively expresses the P bcrA -luxABCDE reporter. DNA-binding and membrane insertion were not affected in the five mutants chosen for further characterization. Homology modelling revealed putative roles for two key residues (R11 and S33) in BcrR activation. Here we present a new model of BcrR activation and signal transduction, providing valuable insight into the functional characterization of membrane-bound one-component systems and how they can coordinate critical bacterial responses, such as antimicrobial resistance.